2019
DOI: 10.1016/j.ffa.2019.02.008
|View full text |Cite
|
Sign up to set email alerts
|

A rigid local system with monodromy group 2.J2

Abstract: We exhibit a rigid local system of rank six on the affine line in characteristic p = 5 whose arithmetic and geometric monodromy groups are the finite group 2.J 2 (J 2 the Hall-Janko sporadic group) in one of its two (Galois-conjugate) irreducible representation of degree six.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Studying the monodromy group of these sheaves is interesting for its applications to coding theory and also as they give interesting examples of lisse sheaves whose monodromy group is a sporadic simple finite group [KR19]. In [Roj19] it was shown that, if f (x) is a monomial, then the monodromy is either finite, the full symplectic group Sp d−1 (for d odd) or the special linear group SL d−1 (for d even) (more generally, see [KT24, Theorem 10.2.4]).…”
Section: Introductionmentioning
confidence: 99%
“…Studying the monodromy group of these sheaves is interesting for its applications to coding theory and also as they give interesting examples of lisse sheaves whose monodromy group is a sporadic simple finite group [KR19]. In [Roj19] it was shown that, if f (x) is a monomial, then the monodromy is either finite, the full symplectic group Sp d−1 (for d odd) or the special linear group SL d−1 (for d even) (more generally, see [KT24, Theorem 10.2.4]).…”
Section: Introductionmentioning
confidence: 99%